Analisis Perbandingan Metode MAUT dan OCRA dalam Rekomendasi Produk Tabir Surya Terbaik - Harahap, Amran Saleh; Tanjung, Dewi Maulida Sari; Soeb Aripin (ADA Research Center, 2024)
This research aims to conduct a comparative analysis between the MAUT (Multi-Attribute Utility Theory) and OCRA (Order of Comparative Risk Assessment) methods in the context of recommending the best sunscreen products. A Decision Support System (DSS) is employed as the underlying tool for selecting the most suitable products based on predefined criteria. The research findings indicate that both methods yield the same best alternative, which is the product